Survey on Status of Prosthodontists in Nepal, Service Rendered and Their Level of Satisfaction - Maharjan, Shyam K.; Mathema, S. (Journal of Nepalese Prosthodontic Society, 2018)
Purpose: This survey aims to gather cumulative data on Prosthodontists in Nepal, their academic, financial and work status, services rendered and satisfaction level on job, lab support, material availability and work place environment. Material and methods: Online form was developed for the purpose of survey regarding “Status of Prosthodontists in Nepal, Service rendered and their level of satisfaction”. The online survey form was sent to Prosthodontists as per data available in Nepalese Prosthodontic Society. Data analysis was done from response obtained from November 1st to December 25th, 2017. Results: Among the 77 Prosthodontists whom the survey form were sent, 65 Prosthodontists responded (85%). The male were 55% and female 45%, majority of age ranges from 31 to 40 years. 81.5% had Master of Dental Surgery (MDS) degree and 52.3% had post graduation from Nepal. 80% of Prosthodontists are practicing in private institute including dental colleges, hospital and clinics. Among the academic degree, 1 tutor, 36 Assistant Professor, 4 Associate professor and 5 professors were recorded. 50% of Prosthodontists had original research article and case report published. Regarding the job satisfaction, lab support, material availability and working environment, most of them were satisfied. Conclusion: Number of Prosthodontists in Nepal are in growing trend. Most of them are of young age. Prosthodontic services rendered are growing in diverse aspect and most of them were satisfied with their job and work.